Point of Interest Foot Traffic Data and Pandemic-Induced Changes in Mobility Patterns: An Exploratory Analysis of Greater Boston - Gavel, Zachary. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Shan Jiang.; Committee: Sumeeta Srinivasan.; Keyword: Transportation.